Long-term exposure to air pollution and gastrointestinal disease: findings from a nationwide cohort study in China - Yanqi Kou; Shicai Ye; Weimin Du; Zhuoyan Lu; Ke Yang; Liping Zhan; Yujie Huang; Ling Qin; Yuping Yang (BMC Public Health)
Abstract Background and aims Air pollution poses significant risks to human health, but its impact on gastrointestinal (GI) health remains underexplored. This study assesses the long-term effects of air pollution on GI diseases using data from the China Health and Retirement Longitudinal Study (CHARLS). Methods This nationwide cohort study utilized CHARLS data from participants recruited in 2011, followed by surveys in 2013, 2015, 2018, and 2020. Long-term exposure to PM2.5, PM10, SO2, NO2, CO, and O3 was assessed using geocoded residential addresses linked to air quality data. Cox proportional hazards models and subgroup interaction analyses were used to evaluate associations between pollutants and GI disease incidence, adjusting for demographic and behavioral confounders. Results The incidence of GI disease was 21.4% among participants. Long-term exposure to PM2.5 (HR = 1.38, 95% CI: 1.33–1.44), PM10 (HR = 1.31, 95% CI: 1.26–1.36), SO2 (HR = 1.74, 95% CI: 1.68–1.81), NO2 (HR = 1.21, 95% CI: 1.17–1.25), CO (HR = 1.48, 95% CI: 1.42–1.54), and O3 (HR = 0.56, 95% CI: 0.54–0.59) was significantly associated with GI disease. Interaction analyses showed that the effects of pollutants varied by region, residence, smoking, and alcohol use. Urban residents and those living in specific regions experienced stronger associations, likely due to higher pollution levels and different environmental factors. Smokers and alcohol users were also more susceptible to the adverse effects of pollutants. Conclusions Long-term exposure to multiple air pollutants increases the risk of GI diseases, while ozone may potentially offer some protective effects. Public health measures to reduce air pollution, especially in urban areas, and to protect high-risk groups are urgently needed.